Odpowiedzi

2009-11-19T18:25:40+01:00
A) x + (3x - y² + 7 ) = x +3x -y² +7 = 4x -y² +7
b) -a +(2a - 3b -1 ) = -a +2a -3b -1 = a -3b -1
c) -x² + (x² - x -7 ) = -x² +x² -x -7 = -x -7
d) -b³ - (b³ - b² -b ) = -b³ -b³ +b² +b = -2b³ +b² +b
e) (2a - 3b) + (4a-b ) = 2a -3b + 4a - b = 6a -4b
2009-11-19T18:26:48+01:00
A) x + (3x - y² + 7 )=x+3x-y²+7=4x-y²+7
b) -a +(2a - 3b -1 )=-a+2a-3b-1=a-3b-1
c) -x² + (x² - x -7 )=-x²+x²-x-7=-x-7
d) -b³ - (b³ - b² -b )=-b³-b³+b²+b=-2b³+b²+b
e) (2a - 3b) + (4a-b ) = 2a-3b +4a-b= 6a-4b
2009-11-19T18:32:54+01:00
A) x + (3x - y² + 7 ) = 4x-y²+7
b) -a +(2a - 3b -1 )=a-3b-1
c) -x² + (x² - x -7 )= -x-7
d) -b³ - (b³ - b² -b )= -2b³+b²+b = b(-2b²+b+1)
e) (2a - 3b) + (4a-b )=6a-4b=2(3a-2b)


Pozdrawiam! :)